The effect of cutting parameters on the performance of ZTA-MgO cutting tool - Mohd Ali, Afifah; Hamidon, N. E.; Zaki, N. K.M.; Mokhtar, Suhaily; Ahmad Azhar, Ahmad Zahirani; Bahar, Rubina.; Ahmad, Zainal Arifin Azhar (Institute of Physics Publishing, 2018)
The effect of cutting parameters on the performances of ZTA-MgO ceramic cutting tool investigated. The aim of this project is to discover the effect of cutting speed and feedrate on the performance of the ZTA-MgO cutting tool via wear and surface roughness measurement. CNC turning machining performed using the cutting speed, Vc range from 354 to 471 m/min and the feed rate, f 0.1, 0.3 and 0.5 mm/rev while the depth of cut, d is kept constant at 0.2 mm. The flank wear, crater wear, and chipping were measured accordingly using optical microscope, Matlab programming and SEM. Surface roughness of machined stainless steel 316L surface were measured using the surface roughness tester (Mitutoyo MTR097-8. The result showing the increment trend of flank wear with increment of cutting speed and feed rate with the lowest value of flank wear, 0.061 mm achieved at Vc = 354 m/min and f = 0.1 mm/rev while the highest flank wear is 0.480 mm at Vc = 471 m/min and f = 0.5 mm/rev. The increasing pattern also observed in the crater wear results. The lowest area of crater wear is 2.2736 mm2 at Vc = 354 m/min and f = 0.1 mm/rev while the highest value is 4.8524 mm2 at Vc = 471 m/min and f = 0.5 mm/rev. As for the surface roughness, the higher the cutting speed, the lower the average roughness (Ra) value. Cutting speed, Vc = 471 m/min with f = 0.1 mm/rev has the lowest value of Ra which is 0.72µm.